Pelindungan Hukum Bagi Konsumen Dalam Menyampaikan Ulasan Atas Suatu Produk Melalui Platform Media Sosial - Naufal, Daffa Rizqy; Marlyna, Henny; Mahardika, Zahrashafa Putri (Jurnal Hukum & Pembangunan, 2025)
Product reviews on social media have become an essential source of information for consumers and play a significant role in building trust in businesses. However, negative reviews often lead to legal disputes, particularly concerning allegations of defamation under Article 27 paragraph (3) of the ITE Law. This study examines legal protections for consumers in expressing reviews, focusing on the right to freedom of expression as guaranteed by Articles 28E paragraphs (2) and (3) and Article 28F of the 1945 Constitution, Law No. 39 of 1999, Law No. 12 of 2005, Article 19 of the UDHR, and the ICCPR. Additionally, Article 4(d) of the Consumer Protection Law recognizes consumers’ rights to express opinions and complaints. Using a doctrinal method, the study reveals inconsistencies in legal practice. The Supreme Court Decision No. 6057 K/Pid.Sus/2022 protects fact-based criticism, while the North Jakarta District Court Decision No. 1265/Pid.Sus/2023 criminalizes reviews deemed defamatory. The study highlights the importance of educating consumers on responsible expression and the need for more consistent regulations to balance freedom of expression and reputation protection in the digital era.